Desenvolvimento de pastas de cimento flexíveis para poços de petróleo submetidos à injeção de vapor utilizando látex do tipo SBR - Oliveira, Filipe Silva de (2011)
Novel cementing materials formulations containing flexible polymeric admixtures have been studied aiming at improving the mechanical behavior of oil well cement slurries submitted to steam injection. However, research activities in this sector are still under development. The steam injected directly into the well causes casing dilation, which after a reduction in temperature, tends to return to its original dimensions, resulting in crack formation and hydraulic isolation loss of the well, which will result in shortening of well life. In this scenario, the objective of the present study was to evaluate the mechanical behavior of Portland-based slurries containing SBR latex, applied in oil well cementing of wells submitted to steam injection. Were formulated slurries with densities of 1.797 g/cm3 (15.0 lb/Gal) and 1.869 g/cm3 (15.6 lb/Gal), containing admixtures with a latex concentration of 0; 66.88; 133.76; 200.64 and 267.52 L/m3 (0, 0.5, 1.0, 1.5 and 2.0 gpc). Tests including rheology, fluid loss control, thickening time, API compressive strength and splitting tensile strength, beyond steam injection simulation. Microstrutural characteristics of the slurries were also performed (XRD, TG, FTIR and SEM). The results showed that increasing the polymer concentration increased in the rheological properties and fluid loss, and a decrease in the elasticity modulus of the cement slurries. The results obtained showed that the slurries can be applied in cementing operations of oil wells submitted to steam injection.